Ferroelectric domain evolution in a Ba(Zr0.2Ti0.8)O3-0.5(Ba0.7Ca0.3)TiO3 piezoceramic studied using piezoresponse force microscopy - Jiang, Xijie; Dietz, Christian; Liu, Na; Rojas, Virginia; Stark, Robert W. (Applied physics letters, 2021)
Lead-free Ba(Zr0.2Ti0.8)O3-0.5(Ba0.7Ca0.3)TiO3 (BZT-0.5BCT) ceramics have drawn attention in recent years because of their outstanding dielectric and electromechanical properties, such as a piezoelectric coefficient d33 ∼ 620 pC N−1 and a large signal of d 33 * ∼ 1100 pm V−1 at 0.5 kV mm−1 at room temperature (RT). These particular properties are relevant to a range of applications. However, the structural origin of this high piezoelectric coefficient is still a subject of discussion. An in-depth understanding of the ferroelectric domain evolution of BZT-0.5BCT ceramics is crucial for probing the underlying mechanisms and for guiding practical applications. Using piezoresponse force microscopy (PFM), we have directly visualized the evolution of the BZT-0.5BCT domain structure using temperature and electric field stimulation on micrometer and nanometer scales. The PFM results unambiguously evidence the coexistence of wedge-shaped and lamellar domains with miniaturized nanodomain structures at RT. The temperature- and electric-field-dependent PFM study presented here highlights the critical role of wedge-shaped domains in domain evolution. Wedge-shaped domains turn into small domains with curved domain walls after the heating cycle and then become lamellar domains after the poling cycle at RT. Transitional domain structures with an increased density of nanodomains appear in both the thermal and poling cycles. More interestingly, the electric-field-dependent domain structure evolution at different temperatures shows better domain structure reversibility at high temperatures than at temperatures close to the phase boundary. This demonstrates that the BZT-0.5BCT ceramic has superior stability at medium temperatures (40 °C–60 °C), implying excellent stability for applications.